The Effect of Six-Weeks Aquatic Exercise Therapy on Static Balance, Function oOf Trunk And Pelvic Girdle Muscles, Pain, And Disability in Woman With Chronic Low Back Pain - Ali Yalfani; Leila Ahmadnezhad; Behnam Gholami; FatemeF Mayahi (Iranian Association of Health Education and Health Promotion, 2017)
Background and Aim: LBP is one of the most important health problems and the main cause of people's disability in most countries that has reached a stage of the epidemic. The aim of this study was to evaluate the effect of six-weeks aquatic exercise on pain, disability, static balance and function of the trunk and pelvic girdle muscles in women with chronic low back pain.  Methods: The statistical population of this study were selected among 20 to 40 year old woman who referred to orthopedic clinics in Hamadan. This is a semi-experimental research. A total of 24 female patients with chronic low back pain were involved in the study and randomly were divided into two groups of 12 individuals: experimental and control groups. The tools for measuring the data were 2 standard questionnaires including Quebec Pain and Oswestry Disability, and also Stork Equilibrium, Seats Up Test, Sorensen Test, and Scott Test. The experimental group performed a six-week training protocol (three sessions per week), and during this period, the control group did not perform any practice. Evaluation and measurements were performed before and after the intervention. In order to analyze the data, using SPSS 19, dependent and independent t-test were used at a significant level of 0.05.  Results: The results of t-test showed that the experimental group had significantly improved dependent variables (p <0.05). However, no significant improvement was observed in control group and the independent t-test showed that there was a significant difference in the change of variables between two groups (P ≤ 0.05).  Conclusion: The results of this study demonstrated that the aquatic therapy protocol used in this study can be an effective therapeutic method to improve the physical condition, health, pain, disability, and patients' balance.